Struktur Nafkah Rumahtangga Petani Transmigran : Studi Sosio-Ekonomi di Tiga Kampung di Distrik Masni Kabupaten Manokwari - P. Tulak, Paulina; Hadi Dharmawan, Arya (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2009)
Among the primary objectives of transmigration program are to increase the economic status of transmigrant farm-households and enhancing rural infrastructures of the local region. To see wether such objective is attainable, a study of transmigrant farm households has been conducted in West Papua. The study attempts: (1) to know whether there is any relation between the socio-cultural/ethnical background of the transmigrant farm-household with the achievement of welfare status, (2) to analyze factors influencing to the income level of transmigrant farm-households, and (3) to understand how the farm households enhance the degree of economic status by building numerous livelihood strategies. The methods as used in the analysis are: (1) income level analysis of the households, (2) gini-ratio analysis, and (3) descriptive analysis. The results of this study are: socio-cultural (ethnical) setting of transmigrant has a substantial influence to the achievement of welfare level. Javanese transmigrant showed a much higher income achievement due to their strong engagement in the non-farm economy, as compared to Papuanese transmigrant farm-households. The non-farm economy provides a strong basis for economic growth at household level. However, the growth of non-farm economy unexpectedly caused an increasing tendency of income disparity among different farm household strata. Since non-farm economy shares a positive contribution for regional economic growth, the study concludes, that the government needs to take seriously this economic sector into account when regional development needs to be well-accomplished in West Papua.